RANCANG BANGUN SISTEM KENDALI LAMPU RUMAH BERBASIS ANDROID MENGGUNAKAN ARDUINO - Tedi Sumardi Tedi; Siti Nurasiah (STMIK SUBANG, 2021)
Home light control system is made to make it easier for residents in controlling the home light practically and efficiently while it on/off. The system is designed using Bluetooth that connect to ATmega328 microcontroller as a main component. The design steps consist of identification and analysis of demands, hardware dan software design, device manufacturing, and testing. The controller system worked when the module bluetooth is connected between smartphone and ATmega328. The results showed that the testing of this home light controller system can work as well as working principle that have been designed.